LINGUISTICS IN THE DIGITAL AGE: PROBLEMS OF UNDERSTANDING THE SOCIAL CONTEXT IN THE TEXTS OF “AL-FAIQ FI GHARIB AL-HADITH” BY ABU AL-QASIM AL-ZAMAKHSHARI - Mohammad Mahmoud Ahmad (ARAB TILI GLOBALLASHUV DAVRIDA: INNOVATSION YONDASHUVLAR VA O‘QITISH METODIKASI MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2025)
The article discusses the complex relationship between the era of digitalization and the study of gharīb al-ḥadīth texts, focusing on al-Zamakhsharī’s work “Al-Fāʾiq fī Gharīb al-Ḥadīth.” It emphasizes that a proper understanding of these texts fundamentally depends on awareness of the social and cultural context in which they were produced, a concept referred to as “fiqh al-lughah” (linguistic jurisprudence). The article demonstrates that rapid and decontextualized digital engagement often leads to the fragmentation of the text and the loss of context, resulting in incomplete or erroneous interpretations of meaning.To address this issue, the article calls for the adoption of innovative technological solutions, such as the creation of multi-layered contextual databases and analytical tools based on artificial intelligence that link lexical items to historical and geographical information. Such approaches ensure a balance between ease of digital access and the depth of traditional scholarly understanding.